Fiber glass composite laminates (FGCL) measurement using 3 axis pulse echo scanning unit - Mahmod, M.F. (Penerbit UTM Press, 2015)
Ultrasonic is a common non-destructive testing for composite laminates inspection. However, high cost caused limited budget organization to own this equipment for their research activities. Our work seeks to develop an automated and reliable ultrasonic scanning unit with affordable cost. The validation of scanning speed using Arduino UNO Microcontroller has successfully achieved by determined the stepping mode. This prototype is suggested to inspect surface defect on glass fiber composite laminates up to 6 mm in thickness as the probe limitation for optimum scanning performance. The optimum scanning speed for this prototype was 12 mm/sec using micro step setup while the average percentage of different against ten times inspection are as low as five percent. Â© 2015 Penerbit UTM Press. All rights reserved.